The impact of article 12 of the convention on the rights of persons with disabilities on Qatar´s private law - Patricia Cuenca Gómez; María del Carmen Barranco Avilés; María Laura Serra; Javier Ansuátegui Roig; Pablo Rodríguez del Pozo (Age of Human Rights Journal, 2017)
Article 12 of the Convention on the Rights of Persons with Disabilities provides that persons with disabilities are entitled to full legal capacity on an equal basis with others and obliges State Parties to provide access to the support that they may require exercising this legal capacity. This paper analyzes the main implications of this Article and its impact on Qatar´s legal system, focusing on the general regulation of legal capacity and provisions in the domain of Private Law, including Family Law. We examine how Qatar´s legislation needs to be adapted to the new paradigm of the CRPD, overcoming preconceptions based on the medical model and assistencialism, which is focused on protection, and moving towards the social model and the human rights approach, aimed at promoting the autonomy of persons with disabilities. To comply with Article 12, Qatar must review the legal provisions that allow the deprivation or restriction of legal capacity on the basis of disability and that require “be[ing] of sound of mind” as a condition to perform legal acts or to exercise rights. Qatar must also take action to replace regimes of substituted decision-making with supported decision-making – extending some support mechanisms available in current legislation – and to ensure the respect of the person’s will and preferences.